2021
DOI: 10.3758/s13423-021-02025-5
|View full text |Cite
|
Sign up to set email alerts
|

Is probabilistic cuing of visual search an inflexible attentional habit? A meta-analytic review

Abstract: AbstractIn studies on probabilistic cuing of visual search, participants search for a target among several distractors and report some feature of the target. In a biased stage the target appears more frequently in one specific area of the search display. Eventually, participants become faster at finding the target in that rich region compared to the sparse region. In some experiments, this stage is followed by an unbiased stage, where the target is evenly located across all regions of the display. Despite thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…On the other hand, across our experiments, we found that the overall RT advantage on high- versus low-probability quadrant targets dropped by roughly 50% between the last epoch of the learning phase and the first epoch of the extinction phase, and dropped further during the extinction phase. This finding closely replicates the results reported by Giménez-Fernández et al (2021) in a recent meta-analytic review of 42 studies. These authors suggested “that participants tend to reduce their bias to the previously rich quadrant as they accumulate more and more evidence that the target is evenly distributed” (p. 9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, across our experiments, we found that the overall RT advantage on high- versus low-probability quadrant targets dropped by roughly 50% between the last epoch of the learning phase and the first epoch of the extinction phase, and dropped further during the extinction phase. This finding closely replicates the results reported by Giménez-Fernández et al (2021) in a recent meta-analytic review of 42 studies. These authors suggested “that participants tend to reduce their bias to the previously rich quadrant as they accumulate more and more evidence that the target is evenly distributed” (p. 9).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings resolve the recent debate about whether target probability cueing is long-lasting or instead rapidly wanes (Jiang, 2018 vs. Giménez-Fernández et al, 2021, respectively). On the one hand, we found search slopes to be consistently shallower when the target appeared in the high- than in a low-probability quadrant during extinction.…”
Section: Discussionsupporting
confidence: 81%
“…To sum up, probabilistic cuing has been proposed to represent an attentional habit because it is gradual, implicit, persistent, viewer centered, transferable only to other serial search tasks, and insensitive to WM load. Previous studies carried out by some of us showed no evidence that probabilistic cuing is implicit, persistent, or gradual (Giménez-Fernández et al, 2020; Giménez-Fernández, Luque, et al, 2022; Vadillo et al, 2020). In contrast, in the present study, we confirmed that probabilistic cuing is not easily hindered by a WM task, although we found some evidence that the expression of this attentional bias might depend on spatial WM resources.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, these studies usually have very small samples that do not grant sufficient statistical power to detect changes in attentional bias between stages. Recently, we have shown that by boosting statistical power, either by increasing the number of participants or by aggregating all available data in a meta-analysis, it is possible to detect a clear decrease in the bias across the unbiased stage (Giménez-Fernández et al, 2020, 2022).…”
Section: Inflexibilitymentioning
confidence: 99%